2015
DOI: 10.1002/evan.21464
|View full text |Cite
|
Sign up to set email alerts
|

Sleep intensity and the evolution of human cognition

Abstract: Over the past four decades, scientists have made substantial progress in understanding the evolution of sleep patterns across the Tree of Life. Remarkably, the specifics of sleep along the human lineage have been slow to emerge. This is surprising, given our unique mental and behavioral capacity and the importance of sleep for individual cognitive performance. One view is that our species' sleep architecture is in accord with patterns documented in other mammals. We promote an alternative view, that human slee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
99
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 103 publications
(105 citation statements)
references
References 105 publications
4
99
0
1
Order By: Relevance
“…Thus, human allo -grooming for parasite removal seems to represent a phylogenetic outlier, consistent with the fact that humans have less body hair, and most of the study populations have some access to efficient grooming technology (combs, etc.). Other recent studies provided stronger evidence for outlier status of human feeding time (Organ et al, 2011) and sleep duration (Samson and Nunn, 2015) as these observed times fell entirely outside the range of expected values. Given our weaker results, combined with the variation across our study populations and the fact that the least acculturated Pumé hunter-gatherers with little sanitary technology are arguably most representative of ancestral conditions, any deviation from typical primate grooming time seems to be fairly recent.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Thus, human allo -grooming for parasite removal seems to represent a phylogenetic outlier, consistent with the fact that humans have less body hair, and most of the study populations have some access to efficient grooming technology (combs, etc.). Other recent studies provided stronger evidence for outlier status of human feeding time (Organ et al, 2011) and sleep duration (Samson and Nunn, 2015) as these observed times fell entirely outside the range of expected values. Given our weaker results, combined with the variation across our study populations and the fact that the least acculturated Pumé hunter-gatherers with little sanitary technology are arguably most representative of ancestral conditions, any deviation from typical primate grooming time seems to be fairly recent.…”
Section: Discussionmentioning
confidence: 85%
“…Human grooming time could therefore represent a phylogenetic outlier (Nunn and Zhu, 2014) if humans spend less time grooming than expected based on typical primate patterns (Prediction 1). This would be similar to decreases in feeding time due to cooking (Organ et al, 2011) and sleep duration due to increased vigilance and opportunity costs (Samson and Nunn, 2015). …”
Section: Introductionmentioning
confidence: 87%
“…Tools were invented; clocking system was developed, enabled the regulation of daily working hours to get the most out of daylight; also eating habits changed, and resulted in a cognitive development. 4 In time, accumulation of goods, arts, and knowledge occurred, generating the manufacturing periods and the evolution of distinct economic systems. We can emphasize that the 1600s and 1700s generated many basic advancements in science, technology, sociology, and economics, and created the era of an inclined economic growth rate, relative to that of the previous.…”
Section: Basic Concepts In Biophysical Economicsmentioning
confidence: 99%
“…She suggests that this could be due to the different scaling rules for cortical neuron density in primates compared to non-primates. In another new comparative study, however, Sampson and Nunn [2015] argue that humans have evolved to need significantly less sleep than their non-human primate relatives. They observe that the human sleep quota 'is the shortest recorded among primates', and they use a phylogenetic outlier test to determine that the human value falls significantly outside the expected range.…”
mentioning
confidence: 99%
“…They also observe that the reduced sleep time is associated with a significantly higher ratio of REM to non-REM sleep in humans. According to Sampson and Nunn [2015], lying down to sleep securely on a platform, nest or on the ground -a behaviour that evolved in the common ancestor of all great apes -may have been the trigger for the evolution of 'deeper' and more efficient sleep, enabling humans ultimately to reduce time spent asleep and thereby increase time available for other activities. Perhaps the increased intensity of sleep in humans reflects an enhancement of the physiological mechanism for clearing metabolites and permitting the benefits of sleep to be realised in a shorter time.…”
mentioning
confidence: 99%